Cross-border resource management : theory and practice - Guo, Rongxing (Developments in environmental science, 2005)
This essay is about the management of natural and environmental resources in cross-border areas. It explores a group of geographical, political, legal, economic and cultural factors that arise when political units (such as sovereign countries, dependent states and other administrative units) seek to utilize natural and environmental resources efficiently and equitably while minimizing the resultant damages (for example, prevention of resource degradation and preservation of the physical environment). This study considers various types of cross-border areas - at both international and sub-national levels. The main objectives of this book are: - To clarify how natural and human systems interact in cross-border areas under conditions of uncertain, imperfect information and, in some circumstances, irreversibility; - To identify and, where possible, quantify the various impacts of 'border' on the environmental activities in cross-border areas; - To evaluate the costs and benefits of cross-border cooperation in the exploitation and utilization of natural and environmental resources; and - To recommend measures in improving national and international legal and regulatory mechanisms for resource exploitation and environmental protection in cross-border areas. * Examines various types of cross-border areas at both international and sub-national levels throughout the world as well as their geographical, political, economic and cultural influences on the cross-border resource management * Uses the latest international and area data, resulting in new findings for cross-border environmental activities * Contains a large number of case studies throughout the world including four in-depth case studies of cross-border resource management.